Team Games Tournament (TGT) Learning Model to Improve Students' Abilities and Motivation Junior High School - Indi Astrina; Muh. Adnan Hudain; Juhanis Juhanis (ETDC: Indonesian Journal of Research and Educational Review, 2026)
Many eighth-grade students at Junior High School 37 Makassar face obstacles in mastering volleyball skills and have low learning motivation during physical education lessons. Conventional learning approaches are considered less able to create active participation and enthusiasm in practicing basic volleyball techniques. This study aims to improve volleyball skills and student learning motivation through the implementation of the Team Games Tournament (TGT) learning model. This study uses the Classroom Action Research method, which is implemented in three stages, namely pre-cycle, Cycle I, and Cycle II. The subjects of the study were eighth-grade students of Junior High School 37 Makassar. Data was collected through observation sheets, volleyball skills tests, motivation observation sheets, and documentation. Data analysis was carried out descriptively by combining quantitative and qualitative approaches. The research findings show a consistent increase in each cycle. In the pre-cycle stage, students' skills and motivation were in the moderate category. After the implementation of the TGT model, the results in Cycle I began to show improvements and reached a peak in Cycle II, where volleyball skills and students' learning motivation increased significantly. This study shows that the TGT model is effective as a learning strategy to improve both physical performance and psychological aspects of students. These results can be a reference for physical education teachers in implementing a competitive but fun cooperative learning model to achieve curriculum targets.